Clinical, Neurophysiological, and MRI Markers of Fampridine Responsiveness in Multiple Sclerosis—An Explorative Study - Mamoei, Sepehr; Jensen, Henrik Boye; Pedersen, Andreas Kristian; Nygaard, Mikkel Karl Emil; Eskildsen, Simon Fristed; Dalgas, Ulrik; Stenager, Egon (Frontiers in Neurology, 2021)
Objective: Persons with Multiple Sclerosis (PwMS), already established as responders or non-responders to Fampridine treatment, were compared in terms of disability measures, physical and cognitive performance tests, neurophysiology, and magnetic resonance imaging (MRI) outcomes, in a one-year explorative longitudinal study. Materials & Methods: Data from a one-year longitudinal study were analyzed. Examinations consisted of the Timed 25-Foot Walk Test (T25FW), Six Spot Step Test (SSST), Nine-Hole Peg Test (9-HPT), Five Times Sit-to-Stand Test (5-STS), Symbol Digit Modalities Test (SDMT), transcranial magnetic stimulation (TMS) elicited motor evoked potentials (MEP) examining central motor conduction times (CMCT), peripheral motor conduction times (PMCT) and their amplitudes, electroneuronography (ENG) of the lower extremities, and brain structural MRI measures. Results: Forty-one responders and eight non-responders to Fampridine treatment were examined. There were no intergroup differences except for the PMCT, where non-responders had prolonged conduction times compared to responders to Fampridine. SSST was associated with CMCT throughout the study. After one year, CMCT was further prolonged and cortical MEP amplitudes decreased in both groups, while PMCT and ENG did not change. Throughout the study, CMCT was associated with the Expanded Disability Status Scale (EDSS) and 12-Item MS Walking Scale (MSWS-12), while SDMT was associated with number of T2-weighted lesions, lesion load, and lesion load normalized to brain volume. Conclusions: PMCT is prolonged in non-responders to Fampridine when compared to responders. TMS-elicited MEPs and SDMT can be used as markers of disability progression and lesion activity visualized by MRI, respectively. ClinicalTrials.gov identifier: NCT03401307